Bukhta u mysa Mogilʹnago na ostrovi︠e︡ "Kilʹdin" / Izdanīe Glavnago Gidrograficheskago Upravlenīi︠a︡ Mgo Vstva - Soviet Union. Gidrograficheskoe upravlenie (Petrograd : Morskoe ministerstvo, Glavnoe gidrograficheskoe upravlenie SSSR; [Петроград] : Морское министерство, Главное гидрографическое управление СССР, 1922)
Mal. korr. I-1906, 07, 08, 09, 10, 11 Bolʹsh. korr. I-1912, 20, 21; Мал. корр. I-1906, 07, 08, 09, 10, 11 Больш. корр. I-1912, 20, 21.; Shows Bukhta Mogil'naya in Ostrov Kil'din, Murmansk Oblast, Russia.; Relief shown by form lines. Depths shown by soundings.; Greenwich meridian.; Title translation: Bay at Cape Mogil'nyy on Kildin Island.; Top margin title translation: Northern Arctic Ocean, Murmansk coast.; "Masshtabʺ 1/2100 ili 25 sazh. 7-ti fut mi︠e︡ry vʺ di︠u︡ĭmi︠e︡." = Scale 1/2100 or 25 7-foot fathoms in 1 inch.; Includes illustrations.; "No. 431" -- corner margins Color; 1:2,100